2020
DOI: 10.1016/j.ctro.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Nodal recurrence patterns on PET/CT after RTOG-based nodal radiotherapy for prostate cancer

Abstract: Biochemical failure after external beam radiotherapy (RT) for node-positive prostate cancer (PC N+) frequently involves nodal recurrences, in most cases out of field. This raises the question if current RTOG-based elective nodal fields can still be considered optimal. Modern diagnostic tools like PSMA PET/ CT and choline PET/CT can visualize nodal recurrences with unprecedented accuracy. We evaluated recurrence patterns on PET/CT after RT for PC N+ , with the aim to explore options for improved nodal target de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Lymphatic drainage of the prostate is complex and lymph node metastases are found in hypogastric and internal iliac nodes (lateral pathway), obturator fossa nodes (inferior pathway), external iliac nodes (ascending pathway), presacral nodes (posterior pathway), and in the common iliac nodes. 2,5,[17][18][19] However, the proPSMA trial 42 showed that in some cases uptake in the nodes was outside the traditional boundaries of an extended pelvic Review lymph node dissection. Translating this finding to the radiation-oncology community implies the use of vascular anatomy instead of the bony anatomy and inclusion of common iliac nodes, which has also been proposed in published reviews.…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphatic drainage of the prostate is complex and lymph node metastases are found in hypogastric and internal iliac nodes (lateral pathway), obturator fossa nodes (inferior pathway), external iliac nodes (ascending pathway), presacral nodes (posterior pathway), and in the common iliac nodes. 2,5,[17][18][19] However, the proPSMA trial 42 showed that in some cases uptake in the nodes was outside the traditional boundaries of an extended pelvic Review lymph node dissection. Translating this finding to the radiation-oncology community implies the use of vascular anatomy instead of the bony anatomy and inclusion of common iliac nodes, which has also been proposed in published reviews.…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
“…51 Because the upper border excludes common iliac nodes and parts of the external iliac and presacral nodes, 7 major lymph node areas at risk were missed for the whole pelvis radiotherapy group, 5 with only 33% of these areas covered when compared with the location of lymph node metastases in patients with pelvic nodal recurrences after radical local treatment. 17,18 Even when the upper border was set at the L5-S1 interspace (same as in the RTOG 9413 trial), only 42% of patients with nodal disease would have complete coverage; hence this coverage is probably insufficient to show any benefit from whole pelvis radiotherapy. Conversely, raising the upper limit of whole pelvis radiotherapy to the L4/L5 interspace could have prevented more than 90% of the nodal recurrences after definitive radiotherapy, according to a retrospective analysis on 2694 patients at Memorial Sloan Kettering Cancer Center (New York, NY, USA).…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pattern of failure analyses after pelvic ENRT have shown that with current treatment field recommendations a relevant proportion of LN are inadequately covered, thus e.g. recommending extending the superior border of the treatment field [39] , [40] . However, although prophylactic pelvic RT and extending pelvic treatment fields may benefit some high-risk patients with microscopic tumour cells metastasis in lymph drainage pathways, there might be a proportion of patients who are overtreated, suffering from radiation-induced side effects unnecessarily.…”
Section: Discussionmentioning
confidence: 99%
“…On review of patterns of recurrence after pelvic radiotherapy, a predominant site for lymph node recurrence is within the para-aortic lymph node region. Sites of recurrence are rarely seen within irradiated pelvic lymph node field [11] , [12] . These findings form the basis of the hypothesis being tested in the PEARLS trial – i.e., that encompassing the para-aortic lymph nodes will have a favourable effect on metastasis free survival (MFS).…”
Section: Introduction/rationalementioning
confidence: 99%